THE ISLAMIZATION OF CENTRAL ASIA AND ITS IMPACT ON SINO-CENTRAL ASIAN RELATIONS: CULTURAL AND RELIGIOUS TRANSFORMATIONS ALONG THE SILK ROAD (8TH–13TH CENTURY) - Chu Beibei (International Scientific and Current Research Conferences, 2025)
This paper examines the process of Islamization in Central Asia and its significant impact on Sino-Central Asian relations along the Silk Road. It traces the spread of Islam across Central Asia, focusing on its influence on the region's political, social, cultural, and religious dynamics. By investigating the role of the Silk Road as a primary channel for cultural exchange and religious diffusion, the study highlights the pivotal transformations in the interactions between Central Asia and China during key historical periods, especially the Tang, Song, and Yuan dynasties. Through a detailed analysis, this paper explores the dual impacts of Islamization on both Central Asia and China, offering a cross-cultural comparative perspective that underscores the long-term effects of these interactions. In doing so, it contributes to a deeper understanding of the complex interplay between Islam, culture, and politics across Eurasia during this period.